UFMylation safeguards human hepatocyte differentiation and liver homeostasis by regulating ribosome dissociation - Shuchun Yang; Li Wang; Ran Gao; Yanchang Li; Duo Zhang; Chenxi Wang; Guang Liu; Jie Na; Ping Xu; Xiaoyue Wang; Yuyan Jia; Yue Huang (Cell Reports)
Summary: Ribosomal UFMylation contributes to ribosome heterogeneity and is associated with ribosome-associated quality control at the endoplasmic reticulum. However, the specific pathophysiological functions of ribosomal UFMylation remain unknown. In this study, we systematically demonstrate the significance of UFMylation in the differentiation and maturation of hepatocytes using human embryonic stem cell-derived hepatocyte-like cells and liver bud organoids as experimental platforms. We also develop a strategy to identify UFMylated substrates and confirm that RPL26 is a substrate in the liver. Additionally, we discover that mice with the Rpl26 c.395A>G (p.K132R) mutation are more susceptible to steatosis induced by a high-fat diet. Further investigations reveal a key role of CDK5RAP3 and RPL26 UFMylation in regulating ribosome dissociation. Our findings suggest that ribosome UFMylation serves as an important safeguard for liver development and homeostasis and may represent a potential therapeutic target for nonalcoholic fatty liver disease.